Analytical Hierarchy Process (AHP) for Maintenance Management at Bali Mandara Hospital - Maria Imaculata Goran Mosa; I Nengah Sinarta; I Gusti Agung Putu Eryani (U Karst, 2022)
The absence of an assessment of the level of damage and the condition of the Bali Mandara Hospital building makes the maintenance management plan contained in the umbrella contract only based on the damage that occurred in the previous year. Therefore, it is very difficult to determine which building infrastructure components require maintenance and repair first. This study examines the priority scale of infrastructure maintenance at Bali Mandara Hospital using the Analytical Hierarchy Process (AHP). In this study, researchers used a quantitative-descriptive approach. The assessment of the building condition index value is then determined by the priority scale of each component using the Analytical Hierarchy Process (AHP) method with the help of the Expert Choice Version 11 application and the SWOT Method. The results showed that the index value for the infrastructure condition of the Bali Mandara Hospital building was 89.492 with very good condition criteria and was in zone I, while the highest priority scale was faucets, namely 1,000, and the lowest priority was action on a scale of 0.050, where this priority scale can be used in planning. Standard Operating Procedure (SOP) and efficient maintenance management. So based on the results of this study, with SWOT analysis, maintenance management can develop a more effective and efficient maintenance plan and Standard Operating Procedure (SOP) by the building condition index and existing priority scale.